2016
DOI: 10.1016/j.egja.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the analgesic potency of ropivacaine 0.2% versus ropivacaine 0.5% in transversus abdominis plane block after cesarean delivery

Abstract: To cite this article: Ahmed Zein El Abdein Mohamed (2016) Assessment of the analgesic potency of ropivacaine 0.2% versus ropivacaine 0.5% in transversus abdominis plane block after cesarean deliveryAbstract Background: Transversus abdominis plane (TAP) block provides sensory block from T6 to L1. It is one of the most widely used regional analgesic techniques and important component of multimodal approach for postoperative analgesia in multiple lower abdominal surgeries. Objective: To compare between the analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…A meta-analysis indicated that compared with alternative analgesic techniques, epidural analgesia did not provide additional clinical benefits to patients during laparoscopic colorectal surgery [ 24 ]. TAPB is a novel and effective analgesia for controlling postoperative pain, and it can provide somatic anesthesia for abdominal surgeries [ 25 – 29 ]. It is important to note that the shortcoming of a single injection of local anesthetic is the limited time of regional neural blockade [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis indicated that compared with alternative analgesic techniques, epidural analgesia did not provide additional clinical benefits to patients during laparoscopic colorectal surgery [ 24 ]. TAPB is a novel and effective analgesia for controlling postoperative pain, and it can provide somatic anesthesia for abdominal surgeries [ 25 – 29 ]. It is important to note that the shortcoming of a single injection of local anesthetic is the limited time of regional neural blockade [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…who showed that ropivacaine 0.2% produces similar analgesia compared to 0.5% in TAP block for cesarean sections done under general anesthesia. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve blocks require minimum concentration of local anesthetics. [ 10 ] Due to the enhanced sensory blockade and less toxic profile of ropivacaine compared to bupivacaine, 0.25% ropivacaine was chosen for the study. There were also variations in the pain scores with the dose of local anesthetics and dexamethasone used in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a study conducted by Ahmed Z EL there was no significant difference in analgesic potency between ropivacaine 0.25% and 0.5% concentration. 11 Study conducted by De Oliveira et. al.…”
Section: Introductionmentioning
confidence: 99%